2015
DOI: 10.1369/0022155415600032
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a Mediates the Inhibitory Effect of Hyperoxia on the Transdifferentiation of AECIIs to AECIs

Abstract: ArticlePremature newborns often suffer from hypoxemia and acute respiratory failure. Supplemental oxygen is one of the most treatments for preterm respiratory support. It has been reported that prolonged exposure to hyperoxia results in oxidative stress-induced tissue damage in the lung, such as acute lung injury and bronchopulmonary dysplasia (BPD) (Kugelman and Durand 2011). BPD is a clinical syndrome of chronic respiratory, which can lead to hypoxemic respiratory failure and death. Advance in mechanical ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The present study thus aimed to determine the role of YAP in the proliferation and differentiation of AECIIs and the involvement of the Wnt/β-catenin pathway in this process in BPD. It was demonstrated that YAP expression was decreased in experimental BPD and played a key role in promoting the proliferation and differentiation of AECIIs, consistent with a previous study by the authors on Wnt3a ( 23 ). In addition, it was found that Wnt3a overexpression could compensate for YAP depletion and vice versa; however, neither altered the expression of the other.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study thus aimed to determine the role of YAP in the proliferation and differentiation of AECIIs and the involvement of the Wnt/β-catenin pathway in this process in BPD. It was demonstrated that YAP expression was decreased in experimental BPD and played a key role in promoting the proliferation and differentiation of AECIIs, consistent with a previous study by the authors on Wnt3a ( 23 ). In addition, it was found that Wnt3a overexpression could compensate for YAP depletion and vice versa; however, neither altered the expression of the other.…”
Section: Introductionsupporting
confidence: 90%
“…Previously, the authors reported that Wnt signaling plays key roles in alveolar injury and repair by regulating the proliferation and differentiation of AECIIs ( 22 , 23 ). The Wnt signaling pathway consists of both canonical and noncanonical pathways ( 24 ) involving Wnt proteins, receptors and regulatory factors that control numerous biological processes, including cell proliferation, development and differentiation ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings on the effect of CHIR99021 are in apparent contrast to a recent mouse study, which suggested that Wnt signalling is required to maintain stemness of AEC2 cells, and that Wnt signalling prevents transdifferentiation of AEC2 40,41 . In addition, Xu et al previously showed that the canonical Wnt ligand Wnt3a blocked transdifferentiation of AEC2 to AEC1 42 . To add to the complexity of Wnt signalling during generation of hiPSC-derived AEC2, it was demonstrated that temporary withdrawal of CHIR99021 is associated with iAEC2 maturation 23,39 , whereas maintenance of proliferation requires adding back CHIR99021 39 .…”
Section: Discussionmentioning
confidence: 97%
“…Nuclear translocation of β-catenin and increased Lef1 expression was observed in the lung from neonatal rats exposed to hyperoxia (95 % oxygen) in the alveolar stage (postnatal days 0 to 7) [ 82 ]. Moreover, it has been shown that neonatal hyperoxia increased nuclear β-catenin and decreased alveolar epithelial type II (ATII) cell to ATI cell transdifferentiation [ 84 , 92 ], which is generally considered as a repair process of alveolar epithelial cells following injury. Furthermore, hyperoxia-induced inhibition of ATII to ATI transdifferentiation was recovered by small interfering RNA (siRNA)-mediated knockdown of Wnt3a in vitro [ 92 ].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, it has been shown that neonatal hyperoxia increased nuclear β-catenin and decreased alveolar epithelial type II (ATII) cell to ATI cell transdifferentiation [ 84 , 92 ], which is generally considered as a repair process of alveolar epithelial cells following injury. Furthermore, hyperoxia-induced inhibition of ATII to ATI transdifferentiation was recovered by small interfering RNA (siRNA)-mediated knockdown of Wnt3a in vitro [ 92 ]. However, it has been reported that in the adult mouse lung, β-catenin was induced during ATII cell to ATI cell transdifferentiation in normoxia condition [ 93 , 94 ].…”
Section: Reviewmentioning
confidence: 99%